Edukasi Pencegahan Ispa Dan Menciptakan Lingkungan Yang Sehat di Dusun 3 Batu Menyan Baru Desa Sukajaya Lempasing Kabupaten Pesawaran - EkaTrismiyana; Marlina Agustina; Andi Bunga Silvia; Dian Angen Saputra; Adinda Wulan Adha; Refsi Erpiyana; Raihan Saputra; Imanda Satria; Partur Khorip; Yuniati Yuniati; Budiarti Budiarti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Acute Respiratory Infection (ARI) is a disease that attacks the upper or lower respiratory tract, is usually contagious, and can range from asymptomatic disease and mild infection to severe disease and can cause disease. Environmental cleanliness means creating a healthy environment that is not susceptible to diarrhea, dengue fever, vomiting and various other diseases. This can be achieved by creating a clean, beautiful and comfortable environment. The aim of this activity is to increase respondents' knowledge regarding preventing ISPA and creating a healthy environment. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. ISPA is an infection of the upper respiratory system caused by microorganisms such as bacteria, fungi and viruses. ISPA is easily transmitted through coughing or sneezing. One way to prevent the spread of ISPA is to create a healthy environment.